Ḥukm al-Ḥijāb wa al-Niqāb ʼinda Fuqahāʻ ʼAṣr al-Ḥadīth - Aida Humaira (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2006)
Women problem is never ending discussion. Hijab and Niqab is an important aspect that becomes Ulama debates. This paper described contemporary Ulama and traditional Ulama perspective of the problem.